Fathers’ Representation in Observational Studies on Parenting and Childhood Obesity: A Systematic Review and Content Analysis - Davison, Kirsten K.; Gicevic, Selma; Aftosmes-Tobio, Alyssa; Ganter, Claudia; Simon, Christine L.; Newlan, Sami; Manganello, Jennifer A. (American journal of public health (1971), 2016)
Background. The involvement of fathers in caregiving has increased substantially over the past 30 years. Yet in child and adolescent psychopathology, few studies include fathers as research participants and few present results for fathers separate from those for mothers. We test for the first time whether a similar pattern exists in research on parenting and childhood obesity. Objectives. To conduct a systematic review and quantitative content analysis of observational studies on parenting and childhood obesity to (1) document the inclusion of fathers, relative to mothers, as research participants and (2) examine characteristics of studies that did and did not include fathers. This study presents new data on the number and gender of parent research participants. Search methods. We searched title, abstract, and Medical Subject Headings term fields in 5 research databases (PubMed, EMBASE, Academic Search Premier, PsycINFO, and CINAHL) using terms combining parents or parenting (e.g., mother, father, caregiver, parenting style, food parenting) and obesity (e.g., obesity, body weight, overweight) or obesity-related lifestyle behaviors (e.g., diet, snacking, physical activity, outdoor play, exercise, media use). Selection criteria. We identified and screened studies as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) published between January 2009 and December 2015, examining links between parenting and childhood obesity, including parents or caregivers as research participants, and written in English. We excluded interventions, nonhuman studies, dissertations, conference abstracts, and studies on youths with specific medical conditions. Of 5557 unique studies, 667 studies were eligible. Data collection and analysis. For each of the 667 studies, 4 coders were trained to code characteristics of the study (e.g., publication year, geographic region, journal, study focus) and parent research participants (e.g., parent gender, demographic background, biological relationship with child, and residential status). We established intercoder reliability before coding the full sample of studies (mean Krippendorf’s alpha = .79; average percentage agreement = 94%). Main results. Of the studies, 1% included only fathers. By contrast, 36% included only mothers. Although slightly more than 50% of studies (n = 347) included at least 1 father, only 57 studies reported results for fathers separate from those for mothers. When we combined them with studies including only fathers, 10% of studies overall reported results for fathers. Samples sizes of fathers were small compared with mothers. Of studies with fathers, 59% included 50 or fewer fathers, whereas 22% of studies with mothers included 50 or fewer mothers. The mean sample size for fathers across all eligible studies was 139, compared with 672 for mothers. Overall, fathers represented 17% of parent participants across all eligible studies. Conclusions. This study unequivocally demonstrates that fathers are underrepresented in recent observational research on parenting and childhood obesity. Public health implications. The underrepresentation of fathers in obesity research compromises the development of effective family interventions for childhood obesity prevention. Targeted opportunities and incentives are needed to support research with fathers.